Technology Enhanced Learning and Academic Performance among Postgraduate Students: An Exploratory Study - Kiranmayi. P , Dr. T. Narayana Reddy (Journal of Informatics Education and Research, 2025)
Technology Enhanced Learning (TEL) has become integral to higher education, offering postgraduate (PG) students flexible and accessible learning modalities. Despite its widespread adoption, limited research has focused on the role of TEL engagement in influencing academic performance among PG learners. This study examines the relationship between TEL engagement, which compromising emotional, cognitive and behavioural dimensions and self-reported academic performance in a sample of 300 postgraduate students of Management institutions in Telangana state. Utilizing a cross-sectional survey design, participants completed the validated 7-item TEL engagement scale (TES) alongside demographic measures and reported their current average academic grade percentages. Descriptive analyses revealed moderate to high TEL engagement These findings underscore that the quality of engagement with TEL and not merely usage frequency is a substantive contributor to academic achievement at the postgraduate level. The study advocates for higher educational institutions to design and implement TEL strategies that actively foster emotional interest, cognitive investment and behavioural participation to enhance PG learners’ academic outcomes. Limitations include the reliance on self-reported grades and the study’s cross-sectional nature, prompting calls for longitudinal and mixed-methods research to further elucidate TEL’s impact.